Clinical Spectrum and Outcome of Snake Bite Cases in Western Nepal - Bajracharya, Sujeeta; Joshi, R.; Shrestha, D. B. (Journal of Nepalgunj Medical College, 2017)
Background: Prevalence of snake bite is high in Nepal. However, there is no exact figure of mortality and morbidity associated with snake-bite probably due to poor reporting. Objectives: To study demographic characters of snake bite victims, to see clinical symptoms of the bite, outcome of snake bite, use of ASVS and its associated anaphylactic reaction. Methods: A retrospective observational hospital based study carried out through July- October 2017 of the patients with the history of snake bite and visited to secondary level hospital (Army Hospital) at Nepalganj. Result: Among 169 cases of snake bite between 6 months to 83 years, 49.70% was between 20-54 years. Highest number of cases (n=110) came from local areas of Nepalganj like Manikapur, Alanagar, Fulltegra, Daduwa, Gayatrinagar and Samsherganj. Male victims were 61.53% (n=104) and 38.46% (n=65) were female. Commonest site of bite was in lower limb (n=116), followed by upper limb (n=47), head, neck and trunk. Maximum number of cases came to the center within 90 minutes of bite while only n= 28 came after 180 minutes of bite. Use of tourniquet as first aid was seen in 68% (n=115) and 3 cases came in with incised wound and sucked wound. A total of 97.04% (n=164) were dry bite with 26.62% (n=45) only had suspicion of snake bite (snake not seen due to invisibility or bite other than snake). A majority of cases presented without any other symptoms (with only history of bite), 45.56% had bite marks, 17.16% had pain and swelling at the bite site, 6.7% had bleeding from the site and burning and tingling sensation. A total of 2.95% (n=5) of snake bite cases needed ASVS and one developed ASVS complication. Conclusion: Snake bite is more common in adult male between 20-54 years and the commonest site is lower limb. Maximum number of cases presented within in 90 minutes of bite using tourniquet on the affected limb as first aid. Only small percentage of snake bite required anti-snake venom treatment and its complication rate is high.